2018
DOI: 10.1016/j.jclepro.2018.02.152
|View full text |Cite
|
Sign up to set email alerts
|

Pricing decisions for substitutable products with green manufacturing in a competitive supply chain

Abstract: In this paper, we examine the pricing strategies in a two-stage supply chain with two competitive manufacturers and one retailer. We address six game models: the centralized model (Model I), the MS-Bertrand model (Model II), the MS-Stackelberg model (Model III), the RS-Bertrand model (Model IV), the RS-Stackelberg model (Model V) and the cost-sharing contract model (Model VI) to explore the optimal pricing strategies of substitutable products. We address the optimal green manufacturing level, retail prices, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(42 citation statements)
references
References 44 publications
(49 reference statements)
0
40
0
Order By: Relevance
“…Stucki found that only 19% of the highest energy cost firms have positive marginal productivity of GSC technology investment [12]. Ma, Zhang, Hong, et al considered a two-stage supply chain composed of two manufacturers producing green products and ordinary products, respectively, and one retailer, and studied the price and green degree decision-making models under six modes, including different decision-making sequences and green investment cost sharing [13]. Zhang, Liu, Zhang, et al studied investment in the preservation technology of perishable goods under the monopoly of a manufacturer and a retailer, and proposed a technology investment cost-revenue sharing contract to coordinate the benefits of all parties [14].…”
Section: Green Technsology Investment Of Supply Chainmentioning
confidence: 99%
“…Stucki found that only 19% of the highest energy cost firms have positive marginal productivity of GSC technology investment [12]. Ma, Zhang, Hong, et al considered a two-stage supply chain composed of two manufacturers producing green products and ordinary products, respectively, and one retailer, and studied the price and green degree decision-making models under six modes, including different decision-making sequences and green investment cost sharing [13]. Zhang, Liu, Zhang, et al studied investment in the preservation technology of perishable goods under the monopoly of a manufacturer and a retailer, and proposed a technology investment cost-revenue sharing contract to coordinate the benefits of all parties [14].…”
Section: Green Technsology Investment Of Supply Chainmentioning
confidence: 99%
“…e manufacturer determines the green degree of products and the wholesale price while the two retailers determine the retail prices. As discussed earlier, we investigate the models with three different vertical SC power structures including the manufacturer Stackelberg, the retailer Stackelberg, and the vertical Nash, respectively [14,16]. In addition, Bertrand or Stackelberg competition is applied between the two retailers under different horizontal power structures.…”
Section: The Decentralized Supply Chain Casementioning
confidence: 99%
“…In addition, Bertrand or Stackelberg competition is applied between the two retailers under different horizontal power structures. Table 2 shows that there exist six game theory-based models with different vertical and horizontal power structures [14,16]. Both models in the first row of Table 2 refer to the authority relationships under which the vertical competition is the manufacturer Stackelberg.…”
Section: The Decentralized Supply Chain Casementioning
confidence: 99%
See 1 more Smart Citation
“…In India, the government is planning to electrify most of the new vehicles by 2030, which forces traditional gasoline automobile manufacturers to redesign their products. Other national strategies such as "German industry 4.0" and "Made in China 2025" also show unprecedented determination for the development of green manufacturing [2].…”
Section: Introductionmentioning
confidence: 99%